The Influence of Liquidity Risk on Efficiency in Rural Banks: The Moderating Role of Interbank Borrowing Fund - Meliza Zafrizal; Rubayah Yakob; Low Soo Wah (Asian Academy of Management Journal of Accounting and Finance, 2021)
High competition in Indonesian banking sectors has resulted in the non-survival of rural banks in Indonesia in the long run. The lack of third-party funding becomes one of the most important factors that cause many rural banks to face liquidity risk. Hence, many rural banks use interbank borrowing fund as an alternative source of funding in order to meet their liquidity requirement. Moreover, this risk also leads to many rural banks in Indonesia having to deal with low efficiency problem. This research examines not only the influence of liquidity risk on efficiency but also the role of interbank borrowing fund as a moderator variable. Random effect regression analysis reveals that liquidity risk has negative influence on efficiency. Furthermore, as moderator variable, interbank borrowing fund is shown to enhance the influence of liquidity risk on efficiency. This research becomes guidance for rural banks in managing their liquidity risk and efficiency. In addition, this research also can provide direction for authority in setting some regulation regarding to rural banks’ activities in interbank market.